2015
DOI: 10.1038/srep18629
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of Selenium Nanoparticle with Dictyophora Indusiata Polysaccharide and Its Antiproliferative Activity through Death-Receptor and Mitochondria-Mediated Apoptotic Pathways

Abstract: Bio-functionalized nanoparticles with semiconducting/metallic core encapsulated in a bio- or bio-derived materials are promising for applications in biology and especially in cancer diagnostic and healing. In this report, we report a facile, single-step, first-time synthesis and in-situ functionalization strategy for the preparation of monodispersed selenium nanoparticles (SeNPs) functionalized using a novel polysaccharide (DP1) extracted from Dictyophora indusiata (a fungus). The DP1 functionalized SeNPs (DP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 42 publications
1
48
0
2
Order By: Relevance
“…The microplate was oscillated for 10 min. Measure the value of absorbance by enzymelinked immunosorbent assay at the wavelength of 490 nm [37]. Calculate the relative degree of proliferation of the cells called relative growth rate (RGR) according to the formula.…”
Section: Preparation Of Jp1 Samples For Cellmentioning
confidence: 99%
“…The microplate was oscillated for 10 min. Measure the value of absorbance by enzymelinked immunosorbent assay at the wavelength of 490 nm [37]. Calculate the relative degree of proliferation of the cells called relative growth rate (RGR) according to the formula.…”
Section: Preparation Of Jp1 Samples For Cellmentioning
confidence: 99%
“…Among these nanomaterials, selenium nanoparticles (SeNPs) have garnered a great deal of attention as efficient drug carriers (Liu et al, 2012; Yu et al, 2014; Xia et al, 2015). As a special Se species, the SeNPs are also recognized because of their excellent antioxidant property and disease preventive effects (Torres et al, 2012; Liao et al, 2015). Abundant evidences also support the better biocompatibility, bio-efficacy and lower toxicity of the SeNPs by comparing with inorganic and organic seleno-compounds (Husen and Siddiqi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nature-evolved multiple binding sites of biomolecules in addition with its catalytic properties could facilitate the development of multifunctional nanoparticles (Katz E. and Willner I., 2004). Recently, substantial research efforts were directed towards developing and extending the applications of biomolecules by integrating the biomolecules with biological nanoparticles such as polysaccharides and lipids (Liao W. et al, 2016;Rassu G. et al, 2015) and other types of nanoparticles including metals (Chinen A.B. et al, 2015;Politi J. et al, 2015), metal oxides (Cao Y. et al, 2016;Shahrestani H. et al, 2016) and polymers (Cavalli R. et al, 2011;Lin T.-T. et al, 2016) through various conjugation strategies ( Table 2).…”
Section: Integrated Biomolecule-nanoparticle Systemsmentioning
confidence: 99%
“…These challenges can be potentially solved by conjugation of biomolecules with biological nanoparticle through strategic functionalisation. Liao W. et al (2016) reported that selenium nanoparticles functionalised with a Dictyophora indusiata polysaccharide formed monodispersed nanoparticles with high stability attributed to the high electrostatic repulsion between hydrophilic moieties on the surface of the polysaccharide in comparison with the bare selenium. Moreover, the nanoparticle conjugate exhibited enhanced selectivity and antiproliferative activity by inducing cell apoptosis.…”
Section: Organic-organic Nanoparticle Conjugatesmentioning
confidence: 99%